2017
DOI: 10.1002/cb.1663
|View full text |Cite
|
Sign up to set email alerts
|

Attracting new customers to loyalty programs: The effectiveness of monetary versus nonmonetary loyalty programs

Abstract: What type of reward attracts customers to loyalty programs? Given the increasing importance of loyalty programs, this question matters. Six sequential studies investigated whether monetary rewards universally attract people more than nonmonetary rewards. Results suggest that monetary rewards elicit a very robust attractiveness premium both on the level of individual rewards as well as on the level of entire reward programs. Across different industries, the more monetary loyalty program was consistently perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(116 reference statements)
2
6
0
Order By: Relevance
“…In the existing literature, reward type is classified differently to estimate its effect on the design of reward programs. Most studies simply divide the reward type into economic vs. social (Hanzaee and Esmaeilpour, 2017), direct vs. indirect (Bombaij and Dekimpe, 2020) or monetary vs. non-monetary (Ruzeviciute and Kamleitner, 2017;Sharma and Verma, 2014). The present study supports constructing the reward type as single and plural (McDermott et al, 2008).…”
Section: Reward Typesupporting
confidence: 81%
See 2 more Smart Citations
“…In the existing literature, reward type is classified differently to estimate its effect on the design of reward programs. Most studies simply divide the reward type into economic vs. social (Hanzaee and Esmaeilpour, 2017), direct vs. indirect (Bombaij and Dekimpe, 2020) or monetary vs. non-monetary (Ruzeviciute and Kamleitner, 2017;Sharma and Verma, 2014). The present study supports constructing the reward type as single and plural (McDermott et al, 2008).…”
Section: Reward Typesupporting
confidence: 81%
“…Chen et al (2021) reviewed existing articles related to reward programs and concluded that numerous studies have attempted to explore factors through customers' preferences or adoption of rewards. For example, Ruzeviciute and Kamleitner (2017) investigated the effectiveness of monetary vs. nonmonetary reward programs. Zhu and Lin (2019) highlighted the importance of reward characteristic (utilitarian Loyalty programs in the Chinese market vs. hedonic) when designing a program.…”
Section: Literature Review 21 Reward Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedonic and utilitarian shopping motivations have been used with great success in contemporary research to define behaviour in contexts such as consumer engagement ( Jones et al, 2006;Ruzeviciute and Kamleitner, 2017), technology enhancement (Blázquez, 2014), experience marketing (Tynan and McKechnie, 2009), sustainability (Ozdamar Ertekin et al, 2015) and cultural influences (Giovannini et al, 2015;Kooti et al, 2016). In each of these contexts hedonic and utilitarian motivation are established as powerful discriminating variables.…”
Section: Chinese Fashion Retailmentioning
confidence: 99%
“…For any business, it is imperious to establish how to maintain current customers and attract new customers to buy their goods. Today, researchers are studying the effectiveness of monetary versus non-monetary loyalty programs (Ruzeviciute & Kamleitner, 2017), and have also focused their search on online allegiance behavior. For example, in the field of online games, online game social migration affects game devotion and addiction (Wei et al, 2017).…”
Section: Positivist Consumer Behavior Researchmentioning
confidence: 99%